Effects of spiritual intelligence and emotional intelligence on organizational citizenship behavior : a study on Islamic banks in Malaysia - Anwar, Md. Aftab (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2016)
Bank managers play critical roles in dealing with rapid changes and developments experienced in today's global business environment. Both spiritual intelligence and emotional intelligence play significant roles in helping the managers to deal with the dynamic changes in business environment, particularly in the banking and finance industry. These intelligences have influenced behaviour that affects individuals' work performance. Organizational citizenship behaviour exists among employees who have greater emotional awareness of having better work accomplishments through their spiritual and emotional experiences, and creating meaningful and ethical work environments. These phenomena have not been sufficiently studied especially in the backdrop of recent corporate scandals and ethical violations. This study is an attempt to empirically investigate the effects of spiritual intelligence and emotional intelligence on organizational citizenship behaviour, mediated by personal values in the Malaysian banking industry. The research used survey data collected from 324 managers of Islamic banks operating in Malaysia. The study employed Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) to identify the dimensionality and construct validity of Spiritual Intelligence, Emotional Intelligence, Personal Values, and Organizational Citizenship Behaviour. Structural Equation Modeling (SEM) technique was utilised to test the seven hypotheses that were proposed to answer the research questions. The study found significant positive effects of spiritual intelligence and emotional intelligence on organizational citizenship behaviour. The study also confirms the existence of significant mediating effects of personal values in the relationships among spiritual intelligence, emotional intelligence and organizational citizenship behaviour. The findings provide several implications for the advancement of current theories as well as for relevant policy making and professional practices. The findings will be useful to corporate management in making new policy decisions on employee selection, development and appraisal. Besides, intelligence quotient (IQ) and emotional intelligence (EI), spiritual intelligence (SI) shall be considered as a criterion for effective selection of bank employees. The findings will also be useful for the development of SI dimensions of employees by designing and implementing appropriate HRD interventions. By answering all the research questions, this study contributes to the body of literature on spiritual intelligence and emotional intelligence through advancing the current knowledge of organizational behaviour theories (e.g. affective events theory-AET) and the theory of multiple intelligences.